Green composite Fe₃O₄/CaO (0.5 g) for biodiesel production with preliminary structural, functional and morphological characterization - Rahmawati, Sri; Wahyuni, Sri; Moestiono, Fernando Putra (Universitas Sebelas Maret, 2025)
The development of environmentally friendly heterogeneous catalysts is crucial to support sustainable biodiesel production. This study aims to develop an eco-friendly Fe₃O₄/CaO (0.5 g) composite synthesized from local iron sand of Tulungagung as the Fe₃O₄ source and waste eggshells as the CaO source for potential catalytic applications in biodiesel production. The synthesis was carried out through a simple method while maintaining sustainability aspects by utilizing natural resources and agricultural waste. The composite was characterized using X-ray Diffraction (XRD) to identify the crystal structure, Fourier Transform Infrared Spectroscopy (FTIR) to investigate functional groups, and Scanning Electron Microscopy–Energy Dispersive X-ray Mapping (SEM–EDX Mapping). The results showed that the obtained composite consisted of two dominant phases, namely Fe₃O₄ as the magnetic phase and CaO as the active basic phase, with average crystallite sizes of 10.08 nm and 31.07 nm, respectively, indicating a high degree of crystallinity. FTIR analysis confirmed the presence of characteristic Fe–O and Ca–O functional groups at the wavenumber range of 500–600 cm⁻¹, while SEM images revealed an agglomerated oval-spherical morphology with an average particle size of 57.36 ± 0.85 nm. EDX analysis further confirmed the presence of Fe, O, and Ca elements, with Ca distribution, though relatively small, remaining consistent as active basic sites. The combination of crystalline properties, nanometer-scale morphology, and elemental composition supports the role of Fe₃O₄/CaO as a heterogeneous catalyst that is not only easily separable by a magnetic field but also potentially enhances catalytic activity in transesterification reactions. Therefore, this material demonstrates strong prospects as an environmentally friendly heterogeneous catalyst derived from local resources to support sustainable biodiesel production.